Serum concentration of toxic metals and rare earth elements in children and adolescent. Issue 6 (1st November 2020) - Gaman, Laura; Delia, Corina Elena; Luzardo, Octavio P.; Zumbado, Manuel; Badea, Mihaela; Stoian, Irina; Gilca, Marilena; Boada, Luis D.; Henríquez-Hernández, Luis Alberto
ABSTRACT: Biomonitoring studies are important for quantifying the body burden of pollutants and their possible effects on health. Serum concentration of 42 elements was assessed by ICP-MS in 89 children (7.2 ± 3.4 years old) from Bucharest (Romania). Levels of pollutants were compared with the clinical data obtained from routine blood tests. Clinical parameters were in the physiological range. Deficiencies of manganese, selenium, and zinc were discovered. Blood levels of elements were low. The highest levels were observed among children younger than six years. The sum of iron, selenium, barium, nickel, antimony, and cerium was positively associated with hemoglobin (Spearman rho = 0.217, P-value = 0.041), while the sum of copper, thallium, niobium, and tantalum was negatively associated (Spearman rho = −0.228, P-value = 0.032). Given the inherent sensitivity of the child population, additional studies are needed to assess the effects of these elements on their health.